Characteristics of SPOB Ship Hull Block Design Based on the Plate Supply Requirements - Mustafa, Wahyuddin; Asri, Syamsul; Fachruddin, Farianto; Rizal Firmansyah, Mohammad; Rizki Clausthaldi, Fadhil; Rijal, Ahmad; Jafar, Jasman; Mega Putra, Adzan (International Journal of Metacentre, 2022)
The main process of shipbuilding consists of several stages of work, including design, fabrication (cutting, shaping or forming), block assembly, outfitting, painting, erection, and work on the pier. The block assembly system is very efficient to be used in a ship production process in modern shipyards. In this system, the assembly's efficiency and productivity depend on the design of the block division; hence, it requires an appropriate design. Generally, the feasibility of the block division design still relies heavily on the expertise of experienced designers who has extensive knowledge of shipbuilding. This study uses 2 (two) block division designs which are based on a plate length of 20 feet (6069 mm) and 30 feet (9144 mm). Based on the division, the characteristics of the blocks' weight, number, dimensions and the number of supply plate material requirements can be obtained. The results show that the characteristics of the weight, number and dimensions of blocks for each plate reference length are different. The total material needed for each design is 773,028 kg and 907,212 kg. The effectiveness of supply material requirements for the design with 20 feet plate is better than the design for 30 ft plate, which is 0.31 compared to 0.41.